(untitled) - Bygrave, Jonathan (England, 2007)
What's special about Total English?: Students can measure their progress using the logically structured lessons with can do' objectives; Students will get lots of grammar and vocabulary practice which is all thoroughly reinforced in the Reference' and Review' sections at the end of each unit; Students can learn good study habits with the Lifelong learning boxes; If students miss a lesson they can use the innovative catch up' CD-ROM that has lots of extra practice material.
Keywords: English language,Tiếng Anh thực hành